Argumentação nas atividades de ensino de Física para alunos com deficiência visual: uma revisão sistemática - Jesus, Aline Santos de (2024)
Despite an undeniable improvement in teaching processes, education for students with visual impairments in the area of natural sciences, as well as in other areas, still needs advances. Teaching visually impaired students requires some characteristics from the teacher that make it possible to overcome some obstacles and strongly encourages them to seek new methodologies in their teaching process. In this context, our objective in this research was, based on a systematic review, to analyze which categories of argumentation are used in articles, dissertations and theses focused on Teaching Physics for students with visual impairments. The steps of the systematic review process were carried out, such as defining the research question, locating the study database, establishing the research criteria and searching the chosen databases. The categorization, application and analysis of the exclusion criteria were carried out, as well as the preparation of the critical summary and the presentation of the conclusions. This research is qualitative in nature, with documentary, bibliographic, exploratory and descriptive aspects. After defining the question, a search and analysis of the titles of articles, dissertations and theses was carried out in the database of the Scientific Electronic Library Online (SCIELO) website and theses and dissertations on the Brazilian Digital Library of Theses and Dissertations website (BDTD), the Benjamin Constant Institute (IBC) and the Physics Teaching Research Meeting (EPEF) regarding Physics Teaching proposals and activities for students with visual impairments. We then classified the texts into categories based on the arguments and any teaching resources used in the activities. To analyze the data obtained, we used the content analysis technique. As results, we can point out a predominance, albeit small, of justificative arguments, in addition to a large number of professional master's degree works, focused on the production of activities.